Injury and illness risks during outdoor European athletics championships: analysis of Helsinki 2012 championships - Edouard, P.; Depiesse, F.; Branco, P.; Alonso, J. M. (British Journal of Sports Medicine, 2014)
Objectives To evaluate the improvement in the medical surveillance system, and to continue the identification and analyses of the incidence and characteristics of newly incurred injuries and illnesses during major Athletics Championships, in order to discuss injury and illness risk factors. Design: Prospective recording of newly occurred injuries and illnesses. Setting: The 2012 European Athletics Championships in Helsinki, Finland. Participants: The 1342 registered athletes, and the physicians and physiotherapists from the national team and local organising committee. Main outcome measures: Incidence and characteristics of new injuries and illnesses. Results: Regarding the medical surveillance system, all countries with more than 15 registered athletes (n=30; 60% of 50 national teams) participated in this study covering 1244 athletes (92.7% of 1342 registered), with report forms response rate of 90.7%.Overall 132 injuries were reported, representing an incidence of 97.6 injuries per 1000 registered athletes, and 61 (47%) resulted in time-loss from sport. The main injury diagnoses were hamstring strain, ankle sprain, lower leg strain, and trunk muscle cramps. Overuse (38%) was the predominant cause, but non-contact trauma represent 25% of injury causes. Injury risk was higher in male and increased with age. Injury risk during finals was significantly higher than during qualifying rounds. The highest incidences of injuries were found in combined events and middle- and long-distance events. 27 illnesses were reported, with most of upper respiratory tract infections and gastro-enteritis/diarrhoea. Illness risk factors remains unclear. Conclusions: The injury and illness surveillance system seems to have improved since the first Athletics studies. During elite Athletics Championships, the gender, age, finals and some disciplines seem to be injury risk factors. Illness risk factors remains unclear. Preventive interventions should focus on overuse injuries, hamstring strains, and adequate rehabilitation of previous injuries, and to decrease the risk of infectious diseases transmission (on appropriate event scheduling, appropriate sports clothes on weather conditions and heat acclimatization).